Effects of amniotic epithelial cell transplantation in endothelial injury - Vácz, Gabriella (Interv Med Appl Sci, 2016)
PURPOSE: Human amniotic epithelial cells (hAECs) are promising tools for endothelial repair in vascular regenerative medicine. We hypothesized that these epithelial cells are capable of repairing the damaged endothelial layer following balloon injury of the carotid artery in adult male rats. RESULTS: Two days after injury, the transplanted hAECs were observed at the luminal side of the arterial wall. Then, 4 weeks after the injury, significant intimal thickening was observed in both untreated and cell implanted vessels. Constriction was decreased in both implanted and control animals. Immunohistochemical analysis showed a few surviving cells in the intact arterial wall, but no cells were observed at the site of injury. Interestingly, acetylcholine-induced dilation was preserved in the intact side and the sham-transplanted injured arteries, but it was a trend toward decreased vasodilation in the hAECs’ transplanted vessels. CONCLUSION: We conclude that hAECs were able to incorporate into the arterial wall without immunosuppression, but failed to improve vascular function, highlighting that morphological implantation does not necessarily result in functional benefits and underscoring the need to understand other mechanisms of endothelial regeneration.